2003
DOI: 10.1590/s1516-14392003000300011
|View full text |Cite
|
Sign up to set email alerts
|

Microhardness and chemical composition of human tooth

Abstract: Hardness of human tooth, both in enamel and dentin, has been measured at different sites using a Vicker's diamond. In this work we show that these values are almost constant all along the enamel and dentin thicknesses. Indentations were done from outer enamel surface to inner dentin layer, going through the enamel-dentin junction, both in transverse and longitudinal samples. Geometrical well-shape indentation uniformity was checked both with light and with scanning electron microscopes, and the chemical compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
102
4
13

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(134 citation statements)
references
References 18 publications
15
102
4
13
Order By: Relevance
“…For dentin, the hardness has been reported in the range of 52 to 64 KHN 14,19 or 46 to 53 VHN 15 . The standard deviation of hardness in this study showed a broad variation, similar to previous reports 16 . This broad variation of hardness values can be produced by factors such as specimen preparation, diagonal length reading error 16 , variation in chemical composition 20 , age, and location in the tooth 21 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For dentin, the hardness has been reported in the range of 52 to 64 KHN 14,19 or 46 to 53 VHN 15 . The standard deviation of hardness in this study showed a broad variation, similar to previous reports 16 . This broad variation of hardness values can be produced by factors such as specimen preparation, diagonal length reading error 16 , variation in chemical composition 20 , age, and location in the tooth 21 .…”
Section: Discussionsupporting
confidence: 91%
“…The standard deviation of hardness in this study showed a broad variation, similar to previous reports 16 . This broad variation of hardness values can be produced by factors such as specimen preparation, diagonal length reading error 16 , variation in chemical composition 20 , age, and location in the tooth 21 . In this study, the KHN and VHN values of enamel are in approximately the same range, while dentin obtained KHN values higher than VHN values for every variation of indentation load and time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…İçeriğinde rezin miktarı az olan Enamic ile rezin bulundurmayan Suprinity malzemelerinin ise yaşlandırma sonucu yüzey sertliği değişmemiştir. Ayrıca 270-360 VHN olan mine sertliğine 6 en yakın malzeme, 262 VHN ile Enamic olarak tespit edilmiştir. Dental materyallerin yüzey sertlikleri, aşınma dirençleri ile ilişkili olduğundan yaşlandırma sonrası yüzey sertliğinin değişmesi malzemenin kullanımı sırasında aşınabileceğini gösterebilir.…”
Section: Discussionunclassified
“…5 Eğer malzeme mine ile temas ediyorsa yüzey sertliğinin 270-360 VHN 'ye yakın olması ve değişmemesi beklenmektedir. 6 Dental materyallerin yüzey pürüzlülüğü ve sertliği gibi optik özellikleri de zamanla değişebilmektedir.…”
Section: Introductionunclassified